2023
DOI: 10.1021/acsomega.3c05509
|View full text |Cite
|
Sign up to set email alerts
|

Production of Ultrafine PVDF Nanofiber-/Nanonet-Based Air Filters via the Electroblowing Technique by Employing PEG as a Pore-Forming Agent

Ali Toptaş,
Mehmet Durmuş Çalışır,
Ali Kılıç

Abstract: Particles with diameters smaller than 2.5 μm (PM2.5) can penetrate the respiratory system and have negative impacts on human health. Filter media with a porous surface and nanofiber/nanonet structure demonstrate superior filtration performance compared to traditional nano- and microfiber-based filters. In this study, nanostructured filters were produced using the electroblowing method from solutions containing different ratios of poly­(vinylidene fluoride) (PVDF) and polyethylene glycol (PEG) polymers for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A bimodal approach is being studied to obtain low pressure drop values by increasing the filtration efficiency of filter mats. The nanofibers mixed between the microfibers on the surfaces formed by combining micro and nanofibers with bimodal filter mats increase the filtration efficiency by creating new air channels and prevent the pressure drop from increasing [12,13]. In the study conducted by Lin et al, it was revealed that a bimodal filter showed a high filtration performance (98.43%) when the average fiber diameters were 2.44 and 0.13 μm,…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…A bimodal approach is being studied to obtain low pressure drop values by increasing the filtration efficiency of filter mats. The nanofibers mixed between the microfibers on the surfaces formed by combining micro and nanofibers with bimodal filter mats increase the filtration efficiency by creating new air channels and prevent the pressure drop from increasing [12,13]. In the study conducted by Lin et al, it was revealed that a bimodal filter showed a high filtration performance (98.43%) when the average fiber diameters were 2.44 and 0.13 μm,…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…Therefore, air filtration materials play a fundamental role in protecting individuals by effectively filtering out harmful airborne particles. Currently, fiber air filtration materials are extensively used primarily due to their high permeability and large specific surface area. The main filtration mechanisms of air filtration materials include diffusion, inertia, interception, gravity, electrostatic adsorption, and other filtration mechanisms. The most widely used fiber air filtration material is the melt-blown and spunbond nonwoven, which is enhanced with higher electrostatic forces under the application of the electret process to improve its air filtration efficiency via the electrostatic adsorption mechanism. , However, rapid attenuation of electrostatic forces and limited stability of filtration efficiency are inevitable. These drawbacks not only limit further improvements in filtration efficiency but also induce higher air resistance.…”
Section: Introductionmentioning
confidence: 99%